META-ANALYSIS ON THE RISK OF MALARIA AND RESISTANCE TO ARTEMISININ-BASED COMBINATION THERAPIES (ACTS) - Ibrahim, Ahmed; Adehi , Mary Unekwu; Majimris , Inkab Jatau; Alhaji , Ismaila Sulaiman (Economics and Statistics Research Journal (ESRJ), 2025)
Global efforts to control and eradicate malaria are seriously threatened by the rising incidence of drug resistance among malaria parasites, especially resistance to Artemisinin-Based Combination Therapies (ACTs). With an emphasis on clarifying the patterns, trends, and treatment strategy implications, this dissertation conducts a thorough meta-analysis to assess the risk variables for malaria and ACT resistance. To offer solid statistical insights into the occurrence of resistance and its correlation with other factors, such as geographic location, treatment methods, and parasite genetics, this study synthesizes data from the body of current literature. This research adopts a systematic approach, using a random-effects meta-analysis framework to aggregate findings from peer-reviewed studies conducted between 2002 and 2024. Key outcomes include the pooled prevalence of ACT resistance and the estimated effect sizes of contributing risk factors, such as treatment delays, monotherapy use, and suboptimal adherence to ACT regimens. The analysis revealed a significant increase in malaria risk in populations with reported ACT resistance, with a mean effect size of 1.432 (95% CI: 1.193–1.720, P < 0.001). Substantial heterogeneity was observed among the studies, as indicated by an I² value of 90%.” The results indicate significant regional variation in resistance patterns, with Southeast Asia and parts of Africa showing higher prevalence rates linked to the presence of Plasmodium falciparum mutations, particularly in the kelch13 gene. The results emphasize the urgency of targeted interventions—like better monitoring systems, better diagnostic tools, and compliance with combination therapy guidelines—are needed. To properly modify treatment plans, this study highlights the cruciality of combining genetic surveillance with clinical and epidemiological data. To reduce the likelihood of ACT resistance and preserve the effectiveness of frontline malaria treatments, this dissertation offers researchers, policymakers, and medical professionals’ practical’ insights. Through its rigorous methodological approach and comprehensive analysis, this study contributes to the growing body of evidence on the challenges posed by malaria drug resistance and underscores the urgency of collaborative global efforts to address this public health crisis.